INTENSITAS SERANGAN HAMA DAN PENYAKIT Shorea leprosula Miq TINGKAT SEMAI DI TAMAN NASIONAL KUTAI RESORT SANGKIMA KABUPATEN KUTAI TIMUR - Jumani Jumani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The purpose of this study was to determine the intensity of pests and diseases on Shorea leprosula Miq Shorea seedlings and silvicultural treatments required.Research conducted by the sampling method with 5 subplot size of 1 m x 1 m with a physical analysis of the Shorea leprosula Miq seedling stage. Data were processed using the formula of frequency and intensity of attacks against Shorea leprosula Miq seedling stage.Results of research and observation showed that the research plots of 1 ha with a sampling of 5 sub plot size of 1 m x 1 m at the seedling stage Shorea leprosula Miq sampling observations of 5 subplots of 60 seedlings Shorea leprosula Miq, with a healthy physic as much as 13 seedlings, light attacked 36 seedlings, moderate attacked 8 and 3 dead seedling. Physically leaves seedling were mostly attacked by insects such as grasshoppers and cricket which causes leaf perforated.  Furthermore, from the results of the calculation frequency identification of pests and diseases by 78% and the intensity of pests and diseases by 25.4% which includes damaged, and based on the identification, it has not required the handling of seedlings.